Komunikasi Dakwah Digital Habib Ja’far dalam Podcast Log In dan Respons Remaja Muslim di Rantauprapat - Nur Samsiah Pasya Hasibuan; Ahmad Sampurna (CV Global Research Publication, 2026)
Thisstudy analyzes Habib Husein Jafar Al-Hadar's digital da'wah communication in podcast Log In Season 4 Episode 4, which discusses JavaneseIslamic cultural tolerance. The focus of the study is to map communication styles based on Norton's theory (assertive, friendly, humorous) and the responses of Muslim teenagers in Rantauprapat from cognitive, affective, and conative aspects. The method used is descriptive qualitative with data collection through observation of a 48-minute YouTube video aired on February 21, 2026, semi-structured interviews with four informants, and triangulation of sources and literature from 2018-2025 using MilesHuberman analysis. The findings show that Habib Jafar effectively integrates digital entertainment with the substance of monotheism through contextual humor, such as comparing istigfar and invulnerability, which is in line with the Uses and Gratifications and S-O-R theories. Teenagers' responses tend to be positive, marked by a new understanding of tolerance, a sense of familiarity, and motivation to share content and worship. However, there are notes regarding the risk of misinterpretation in viral clips. Overall, this study confirms the potential of podcasts as a relevant medium for da'wah or Generation Z in the digital era, as evidenced by the achievement of 4 to 6 million viewers in the first 30 days.